Financial Sustainability : The Influence of Internal Efficiency in Indian Commercial Banks - Guru, Smitisikha; Panda, Priyabrata (Prabandhan: Indian Journal of Management, 2024)
Purpose : The paper examined the relationship between internal bank efficiency and financial sustainability within the specific context of Indian commercial banks. The study aimed to provide empirical evidence on the determinants and consequences of internal bank efficiency and its impact on the long-term financial sustainability of Indian commercial banks. Methodology : The panel data consisted of 65 banks for a sample period of 10 years from 2012 to 2021 and was analyzed using panel regression and generalized methods of moments models to analyze the interplay between CAMEL parameters and profitability and stability. Findings : The findings of the study offered valuable insights into drivers of internal efficiency in Indian commercial banks, such as capital sufficiency, asset quality, operational efficiency, cost management, liquidity, and earning efficiency. Practical Implications : The results underscored the significance of augmenting internal efficiency as a means of propelling enduring financial performance, irrespective of the sizes and varieties of banks. Originality : In contrast to earlier studies, the present study highlighted the immediate and long-term effects of internal efficiency variables on the stability and profitability of banks.